Alumina-supported CuO-CeO2-ZrO2 Catalysts for CO Oxidation - Preparation and Characterization - Rattan G.; Prasad R.; Katyal R.C. (My University, 2025)
The effect of catalyst samples, prepared by different methods, having the composition (CuCe5.17Zr3.83Ox/γ-Al2O3 (20 wt%) was studied in the present work for carbon monoxide (CO) oxidation. Cu(NO3)23H2O was used as a precursor for the preparation of the catalysts. Catalysts were prepared by four methods: co-impregnation, citric acid sol-gel, urea nitrate combustion and urea gelation co-precipitation methods. Prepared catalysts were characterized by BET specific surface area, X-ray diffraction, thermogravimetic analysis/differential scanning calorimetry (TGA/DSC) and scanning electron microscopy (SEM) techniques. The oxidation of CO was carried out in a tubular fixed bed reactor at atmospheric pressure and at temperature ranging from ambient to 250°C. A fixed weight (100 mg) of the catalyst was taken and 2.5% CO in air at a total feed rate of 60 ml/min was used in the reactor. It was observed that the performance of the catalysts in CO oxidation was influenced by the preparation methods. The catalyst prepared by sol-gel method that calcined at 500°C exhibited excellent activity for CO oxidation with total conversion at 210°C. The ranking order of the alumina supporting CuO-CeO2-ZrO2 catalysts was as follows: sol-gel > co-impregnation > urea gelation > urea nitrate combustion. The four catalysts prepared did not show deactivation of catalytic activity for 50 h of continuous runs. © 2013 Indian Institute of Chemical Engineers.